Prevalence of anxiety and depression among family members of ICU patients in a tertiary-level hospital in Nepal: A cross-sectional observational study - Regmi, Sadikshya; Pradhan, Bishwas; Acharya, Subhash Prasad; Shrestha, Pramesh Sunder; Pathak, Sunil; Shahi, Sumit (Journal of Nepalese Society of Critical Care Medicine, 2025)
Background and aims: The Intensive Care Unit (ICU) environment places emotional and psychological strain to not only patients but also their families. In Nepal, the psychological impact on family caregivers remains underexplored. This study assessed the prevalence of anxiety and depression among ICU caregivers in a tertiary hospital setting. Methods: A cross-sectional observational study was conducted from September to December 2024, involving 110 primary caregivers of ICU patients. Psychological distress of the caregivers was evaluated using the Nepali version of the Hospital Anxiety and Depression Scale (HADS), with scores ≥11 indicating clinically significant anxiety or depression. Demographic and clinical information was gathered using a structured questionnaire. Logistic regression analyses were used to identify associated factors. Results: Anxiety and depression were present in 57.3% and 37.3% of caregivers, respectively. Anxiety was significantly higher among caregivers of younger patients and those cohabiting with the patient (OR 6.505; 95%CI: 1.188-35.619; p=0.031). Nasogastric tube insertion was associated with increased anxiety (p = 0.017), while tracheostomy correlated with higher depression levels (p = 0.045). Spousal relationship and role as a primary caregiver were also linked to elevated depression. Interestingly, employed individuals experienced more distress than farmers and the unemployed. No significant associations were observed with gender, marital status, education, or type of ICU admission. Conclusion: Family caregivers of ICU patients, particularly co-residing relatives and spouses, face substantial psychological challenges. Tailored interventions, including counselling, improved physician communication, and psychosocial support, are essential to reduce caregiver distress in the ICU setting.